Multiobjective Calibration for Comparing Channel Sediment Routing Models in the Soil and Water Assessment Tool. Issue 1 (1st January 2014) - Lu, Shenglan; Kayastha, Nagendra; Thodsen, Hans; van Griensven, Ann; Andersen, Hans Estrup
Abstract : Sediment transport is important for ecology and water quality in receiving waters. Physically based channel erosion methods were implemented in the Soil and Water Assessment Tool version 2009 (SWAT2009) to improve sediment concentration (SS) results. In the study, the default simplified Bagnold sediment routing method (EQN‐0) and the physically based simplified Bagnold sediment routing method (EQN‐1) were compared with Pareto fronts from multiobjective calibration. Two SWAT models using EQN‐0 and EQN‐1 were set up for a small agricultural Danish catchment and calibrated with multiobjective calibration on daily and weekly flow‐weighted SS (WF SS). Results showed that the Pareto front of EQN‐1 was slightly closer to the optimal point than EQN‐0 in the objective space. Trade‐off between WF SS and daily flow in EQN‐1 was smaller than in EQN‐0. The EQN‐0 method generated more surface erosion to improve WF SS. The EQN‐1 method generated more base flow to improve WF SS. The EQN‐1 method was less dependent on surface erosion and simulated peak and low values of WF SS better than EQN‐0. Therefore, EQN‐1 is more suitable than EQN‐0 in modeling SS in small lowland catchments.